Associations between intakes of foods and their relations to overweight/obesity in 16-year-old adolescents. (7th April 2022) - Tell, Maria Norburg; Hedin, Katarina; Nilsson, Mats; Golsäter, Marie; Lingfors, Hans
Abstract: There is limited knowledge about the associations between intakes of different foods and inconsistency in the literature of the relation between the quality of food intake and bodyweight in adolescents. The aim of this study is to explore how healthy self-reported food intakes are associated with each other and with overweight/obesity in adolescents. This is a cross-sectional study of seven cohorts of adolescents ( n 13 451) who turned sixteen from 2009/2010 up to 2015/2016 and responded to a health questionnaire used by the School Health Services in southeast Sweden. Associations between intakes of ten self-reported foods as well as between food intakes and weight groups based on the International Obesity Task Force standards (isoBMI) were explored by multivariable logistic regression. Healthy intakes of different foods were mostly associated with each other with the strongest association between a high intake of fruit and a high intake of vegetables (odds ratio (OR) = 25 (95 % confidence interval (CI) 20⋅0–33⋅1)). A low-frequency intake of sweets/snacks (OR = 2⋅35 (95 % CI 1⋅84–3⋅00)) was associated with overweight/obesity as well as a healthy choice of butter/margarine (≤40 % fat) (OR = 1⋅82 (95 % CI 1⋅39 to 2⋅41)), but a high-frequency intake of vegetables was negatively associated with overweight/obesity 0⋅77 (0⋅62–0⋅95). To promote health and achieve a healthy weight among adolescents, it is important to take both diet quality and total food amount into consideration.